What is Known About Environmental Cost Accounting? Systematic Literature Review - Citra Dhistia Murti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study evaluates articles dealing with environmental cost accounting to learn a valuable lesson. Design/Methodology/Approach: This study used the review procedure by Hoque (2014) with several analyzes employed in the prior research by Anggraini et al. (2022). Articles were then reviewed and identified by entering the keywords